MANAJEMEN BIMBINGAN DAN KONSELING DALAM PENGEMBANGAN KECERDASAN MORAL SISWA (Studi Deskriptif Kualitatif pada Siswa Kelas XI Jurusan AT-2 SMK Negeri 1 Cugenang) - Neneng Sulastri; Wiwik Dyah Aryani; Yanti Lestari; Akbar Agung Gumelar; Elih Herliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the moral intelligence of students and the role of guidance and counseling in developing it among eleventh-grade students of the Agribusiness Crop Production Program (AT-2) at SMK Negeri 1 Cugenang. A descriptive qualitative approach was employed, with data collected through a five-point Likert-scale questionnaire covering seven moral intelligence indicators, namely empathy, conscience, self-control, respect, responsibility, honesty, and justice, supported by observation and documentation. Twenty-four students took part as respondents, and one representative response was analyzed in depth to illustrate the descriptive qualitative pattern found among the participants. The results show that the students' overall moral intelligence falls into the high category, with a mean score of 3.90; conscience was the strongest indicator (5.00), while self-control was the weakest (3.33). The perceived role of guidance and counseling in developing moral intelligence falls into the moderate category, with a mean score of 3.17, indicating that counseling services, although present, have not been fully optimized. The study recommends strengthening group guidance and individual counseling that specifically target self-control, consistency in responsibility, and the courage to practice honesty in challenging situations.